383-Fall11-Lec14-page26

383-Fall11-Lec14-page26 - P(A | J M = P(A | M No P(B | A J...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
26 Suppose we choose the ordering M, J, A, B, E P (J | M) = P (J)? No P (A | J, M) = P (A) ? P (A | J, M) = P (A | J)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ? P (A | J, M) = P (A | M) ? No P (B | A, J, M) = P (B | A) ? P (B | A, J, M) = P (B) ? Example...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online